Pure spinor superspace identities for massless four-point kinematic factors - Mafra, Carlos R. [UNESP] (Int School Advanced Studies, 2008)
Using the pure spinor formalism we prove identities which relate the tree-level, one-loop and two-loop kinematic factors for massless four-point amplitudes. From these identities it follows that the complete supersymmetric one- and two-loop amplitudes are immediately known once the tree-level kinematic factor is evaluated. In particular, the two-loop equivalence with the RNS formalism (up to an overall coefficient) is obtained as a corollary.
Keywords: superstrings and heterotic strings; superspaces